Vibrio vulnificus RtxA Is a Major Factor Driving Inflammatory T Helper Type 17 Cell Responses in vitro and in vivo - Lee, Arim; Kim, Myun Soo; Cho, Daeho; Jang, Kyung Ku; Choi, Sang Ho; Kim, Tae Sung (Frontiers in Immunology, 2018)
T helper type 17 (Th17) cells are a subset of pro-inflammatory T helper cells that mediate host defense and pathological inflammation. We have previously reported that host dendritic cells (DCs) infected with Vibrio vulnificus induce Th17 responses through the production of several pro-inflammatory cytokines, including interleukin (IL)-1 and IL-6. V. vulnificus produces RTX toxin (RtxA), an important virulence factor that determines successful pathophysiology. In this study, we investigated the involvement of RtxA from V. vulnificus in Th17 cell induction through the activation and maturation of DCs. The increased expression of the DC surface marker CD40 caused by V. vulnificus wild-type infection was reduced by rtxA gene mutation in V. vulnificus. The mRNA and protein levels of Th17 polarization-related cytokines also decreased in V. vulnificus rtxA mutant-infected DCs. In addition, the co-culture of Th cells and DCs infected with rtxA mutant V. vulnificus resulted in reduction in DC-mediated Th17 responses. Th17 cell responses in the small intestinal lamina propria decreased in mice inoculated with V. vulnificus rtxA mutant as compared to those inoculated with the wild-type strain. These decreases in DC maturation, Th17-polarizing cytokine secretion, and Th17 responses attributed to rtxA mutation were restored following infection with the rtxA revertant strain. Furthermore, the mutation in the hlyU gene encoding the activator of rtxA1 gene reproduced the results observed with rtxA mutation. Taken together, V. vulnificus, by means of RtxA, induces inflammatory Th17 responses, which may be associated with adaptive responses of the host against V. vulnificus infection.